THE WHOLE WORLD AROUND ONE BALL (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The world's most viewed sporting event is the FIFA World Cup. The historical evolution of football as a sport, its playing methods, and the possibilities and circumstances established for Uzbek football players are all covered in this article.